2003
DOI: 10.1007/s00431-003-1273-0
|View full text |Cite
|
Sign up to set email alerts
|

Post-natal corticosteroid use

Abstract: There are wide variations in corticosteroid usage. This emphasises the need to identify if there is a corticosteroid dosage regimen with a positive risk/benefit ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
0
12
2
1
Order By: Relevance
“…In addition, postnatal steroids are given to those considered at highest risk, i.e. those who remain ventilator dependent (42) Thus, in at least the majority of infants at very high risk of developing BPD and at an age when they are actively being considered for treatment with systemically administered corticosteroids, ETCO measurements can be made.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, postnatal steroids are given to those considered at highest risk, i.e. those who remain ventilator dependent (42) Thus, in at least the majority of infants at very high risk of developing BPD and at an age when they are actively being considered for treatment with systemically administered corticosteroids, ETCO measurements can be made.…”
Section: Discussionmentioning
confidence: 99%
“…36 Twenty-one percent of British consultant pediatricians reported administering PNSs after the first week of life to ventilated neonates. 37 There have been many commentaries regarding the most appropriate use or nonuse of PNSs. 10 Barrington 31 reviewed 8 reports describing longer-term outcomes of infants enrolled in prospective trials of PNSs to prevent or treat BPD/CLD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other groups using lower doses (Matheny et al, 2004;Mei et al, 2004;Perloff et al, 2004) did not observe a clinically relevant induction of P-gp. We therefore believe that data presented in this communication are also relevant for the multiple dosing scenario and suggest that a potential reason for the neurotoxic effects (O'Shea et al, 1999;Yeh et al, 1998Yeh et al, , 2004Murphy et al, 2001;Nicholl et al, 2002;Williams and Greenough, 2003;Halliday, 2004) seen in preterm babies might be related to an undeveloped BBB. …”
Section: Downloaded Frommentioning
confidence: 81%
“…Murphy et al (2001) have shown that dexamethasone, the most widely used corticosteroid in premature infants, is associated with a significant decrease in cerebral cortical gray matter volume. As a result, concern has been voiced as to whether postnatal therapy with systemically administered dexamethasone is justified (Nicholl et al, 2002;Williams and Greenough, 2003;Halliday, 2004). Although the neurological adverse effects are widely recognized, no mechanism has been postulated for the occurrence of these neurological complications.…”
mentioning
confidence: 99%